International law, human rights and HIV/AIDS - Patterson David; London Leslie (The World Health Organization, 2002)
This article explores the relevance of international human rights law in the response to the HIV/AIDS epidemic at national and international levels. Public health advocates can use arguments based on this body of law to promote responses to HIV/AIDS that reflect sound public health principles and documented best practice. Development assistance is increasingly linked to rights-based approaches, such as participatory processes, and strategic alliances between health professionals, organizations of people living with HIV/AIDS, and affected communities. Legal and human rights advocacy strategies are increasingly productive and necessary.